Bureaucratic Transparency in Regional Budget (APBD) Management - Pradana, I Putu Yoga Bumi (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2015)
This research is motivated by the lack of publication concerning budget management information by the Government of Kupang through online media. This research aims to study the factors that lead to the lack of transparency of budget management information by the Government of Kupang. This study used a qualitative method with instrumental case study and the data collection procedures using in-depth interviews, and documents study. The data validation uses triangulation technique of sources. The research subjects of Kupang Government Bureaucracy are determined purposively. The results show that the rate of secrecy/confidentiality of Kupang Government budget management information is quite high, thus difficult to be accessed by the public (over secrecy). The causes are diverse, among others, problems of socialization, lack of legal instruments governing the infrastructure in the field of public disclosure, lack of resources and a growing perception among the head SKPD and head of the Treasury Division of the Regional Secretariat of Kupang that local financial documents such as RKA, DPA, and the LRA are state confidential documents.